Ibn Khaldun, a 14th-century Moorish Maliki School Judge, and his Natural Law Monetary Theory - Falus, Orsolya; Tunç, Bilal (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
According to Aquinas’s theory, divinity is not absent from natural law theory, as the original creator of the world, God, must be in some sense ultimately responsible for nature and its laws. Starting with this reasoning, it can be stated that God is the source of all values, which is the predominant philosophy and theology of the Islamic world as well. An important feature of this sense of natural law thought has a straight connection to the Islamic Maslaha, which refers basically to the purpose or goal which law is to serve. Maslaha is a concept in Shariah, the traditional Islamic law. It is not equal to Shariah, but rather a notion that belongs to Fiqh as the Islamic jurisprudence. It is one of the secondary sources in Islamic jurisprudence used by some Madhhab to interpret Shariah – the general principles present in the Quran and the Sunnah – in order to set rules. The aim of the present paper is to introduce Ibn Khaldun as a representative of Maliki law school, and his natural legal theory on money, based on his opus magnum (“Al-Muqaddimah”). The research method applied is source analysis.